Kajian Efektivitas Pengobatan pada Pasien Stroke Iskemik di Instalasi Rawat Inap RSUD Nunukan: Study of Treatment Effectiveness in Ischemic Stroke Inpatients Instalation Nunukan Hospital - Rida Wahda Maulida Tahir; Hifdzur Rashif Rija’i; Niken Indriyanti (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Ischemic stroke occurs due to obstruction of the blood vessels that supply the brain. Obstruction occurs due to increased fat lining the blood vessels or atherosclerosis. Atherosclerosis will cause cerebral thrombosis and cerebral embolism. This study aims to examine effectiveness of the use of drugs in ischemic stroke patients hospitalization at Nunukan Hospital. This study is a non-experimental study with a descriptive analysis design using medical record data collected retrospectively and the number of samples in this study was 70 patients. The sample selection of this research was using purposive sampling technique. The results showed tthe highest characteristics of ischemic stroke patients by gender were male (54.29%), based on age group 45-65 years (64.29%), based on diagnoses with comorbidities (64.70%), and the length of treatment the most occurred in 5-10 days (72.55%). The most used drugs single therapy for ischemic stroke are antiplatelet drugs, namely aspirin (28.57%) and the most used combination therapy is piracetam and citicoline (50%). The most frequent drug interactions were aspirin and clopidogrel (48.57%). While the accuracy of drug use includes the right indication (100%), the right drug (94.29%), the right dose (97.14%), and the right frequency (97.14%). Thus, it was concluded that the treatment of ischemic stroke at the inpatient installation the Nunukan General Hospital was effective.